Copper(II) complex-loaded castor oil-based nanostructured lipid carriers used against Mycobacterium tuberculosis: Development, characterisation, in vitro and in vivo biological assays - Sato, M. R. [UNESP]; Oshiro-Junior, J. A.; Souza, P. C. [UNESP]; Campos, D. L. [UNESP]; Pereira-da-Silva, M. A.; Pavan, F. R. [UNESP]; Da Silva, P. B. [UNESP]; Chorilli, M. [UNESP] (Govi-verlag Pharmazeutischer Verlag Gmbh, 2019)
A copper(II) complex-loaded castor oil-based nanostructured lipid carrier was evaluated to enhance the poor water solubility of antimicrobial compounds, improving their biological properties and antimicrobial activity against Mycobacterium tuberculosis. Nanostructured lipid carriers were composed of the castor oil, polyoxyethylene 40 stearate and caprylic/capric triglyceride, poloxamer 407, cetyltrimethylammonium bromide and three different copper(II) complexes. The systems were ultrasonicated at an amplitude of 8% for 20 min and an ice bath was used throughout the procedure. The blank nanostructured lipid carrier (F5) and nanostructured lipid carriers loaded with copper(II) complex 1, 2 and 3 (F5.1, F5.2 and F5.3, respectively) for 45 days presented values of mean diameter, polydispersity index and zeta potential ranging from 186 to 199 nm, 0.14 to 0.2 and 24 to 30 mV, respectively. Atomic force microscopy indicated that the nanostructured lipid carriers were distributed at the nanoscale, corroborating the mean diameter data. Differential scanning calorimetry determined the melting points of the constituents of the nanostructured lipid carriers. The antimicrobial activity of copper(II) complex-loaded F5 against M. tuberculosis H(37)Rv showed better anti-tuberculosis activity than the free complexes. In vivo biological assays of complex-loaded F5 demonstrated reduced toxicity. Our results suggest that nanostructured lipid carriers could be a potential nanotechnological strategy to optimise tuberculosis treatment.